Analysis of Polyethylene Degrading Potentials of Microorganisms Isolated From Compost Soil - Niren Andrew, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Analysis of Polyethylene Degrading Potentials of Microorganisms Isolated From Compost Soil